2002
DOI: 10.1002/ps.558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metabolic detoxifying enzyme activities and insecticide resistance in Frankliniella occidentalis

Abstract: The western flower thrips Frankliniella occidentalis (Pergande) is a very significant pest of a number of different agricultural crops in the south-east of Spain. The importance of thrips as a pest is not due mainly to the direct damage inflicted on the plant, but to the loss in commercial value which occurs as a consequence of the development of dark spots caused by the tomato spotted wilt virus (TSWV) which they transmit. The economic threshold is therefore almost zero, which enhances the problems of resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
5
21
0
Order By: Relevance
“…Insecticide resistance levels have been positively correlated with levels of detoxifying enzymes in several insect pests. In such cases, detoxifying enzymes have been explained as a mechanism of resistance 20, 27, 28. Although resistant populations of field‐collected adults and nymphs displayed significantly higher levels of detoxifying enzymes, detoxifying enzymes may not be the only mechanism of resistance in this case.…”
Section: Discussionmentioning
confidence: 98%
“…Insecticide resistance levels have been positively correlated with levels of detoxifying enzymes in several insect pests. In such cases, detoxifying enzymes have been explained as a mechanism of resistance 20, 27, 28. Although resistant populations of field‐collected adults and nymphs displayed significantly higher levels of detoxifying enzymes, detoxifying enzymes may not be the only mechanism of resistance in this case.…”
Section: Discussionmentioning
confidence: 98%
“…This resistance could be caused by quantitative or qualitative changes in the specific isozymes hydrolysing or sequestering the insecticides 6. In a previous study,28 higher esterase activities were found in resistant populations of F. occidentalis . For the present study, the mean esterase levels towards α‐NA (substrate that is cleaved in insect preparations mainly by carboxylesterases and AChEs)29 and p ‐NPA (considered to be a broad reporter of esterase activity)30 were higher in the resistant strains than in the reference one, in accordance with previous results 28.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study,28 higher esterase activities were found in resistant populations of F. occidentalis . For the present study, the mean esterase levels towards α‐NA (substrate that is cleaved in insect preparations mainly by carboxylesterases and AChEs)29 and p ‐NPA (considered to be a broad reporter of esterase activity)30 were higher in the resistant strains than in the reference one, in accordance with previous results 28. The studies carried out by Jensen11, 12 also showed increased total esterase activities to α‐NA or β‐NA when resistant strains were assayed, compared with a susceptible population.…”
Section: Discussionmentioning
confidence: 63%
“…Such a failure often occurs due to a change in the susceptibility levels of the pest species to synthetic insecticides. Susceptibility degree changes due to metabolic detoxification of the insecticides through higher activity of some detoxifying enzymes under the stress of different management practices (Jensen 1998(Jensen , 2000Komagata et al 2010;Maymo et al 2002;Wu et al 2011). Generally three principal enzymesgeneral esterases (GEs), glutathione-s-transferases (GSTs) and cytochrome P450 mediated monooxygenases (CYPs) -are involved in the process of metabolic detoxification of insecticides.…”
Section: Introductionmentioning
confidence: 99%